Calibration strategies applied to laser-induced breakdown spectroscopy: A critical review of advances and challenges - Costa, Vinicius C. (2020)
Over the years, laser-induced breakdown spectroscopy (LIBS) has been reported in the literature as an alternative to traditional methods of analysis, becoming well established among spectroanalytical techniques. LIBS is a technique widely used for qualitative approaches; however, it is necessary considerable effort for use in quantitative analysis, mainly due to severe matrix effects. These limitations make it difficult to broaden the application of LIBS in quantitative analysis. In this sense, this review discusses recent advances in calibration strategies applied in LIBS for minimizing matrix effects and enabling determination with satisfactory accuracy and precision. Applications, advantages, and limitations of the calibration strategies, such as matrix-matching calibration (MMC), internal standardization (IS), standard addition (SA), multi-energy calibration (MEC), one-point gravimetric standard addition (OP GSA), one-point and multi-line calibration (OP MLC), slope ratio calibration (SRC), two-point calibration transfer (TP CT), single-sample calibration (SSC), multiple linear regression (MLR), principal component regression (PCR), partial least squares (PLS) and artificial neural networks (ANN) are discussed.